DNAzyme-based colorimetric biosensor for rapid detection of Shigella flexneri - Manikandan Murugan; Elangovan Saranya; Mohandass Ramya (Scientific Reports)
Abstract Shigella flexneri, a formidable gram-negative bacterium, that triggers the most contagious form of shigellosis through bloody diarrhea, presenting a significant threat. As a severe foodborne pathogen, it underscores the need for intensified research into more effective prevention strategies and heightened public health awareness. The traditional methods used to detect S. flexneri are time-consuming and inconvenient. As a result, there is a need for accurate and rapid diagnostics in food and water samples. The experimental methods involved modifying S. flexneri-specific HGD-aptamer and employing single-walled carbon nanotubes to develop a colorimetric detection assay exploiting DNAzyme. The HGD-aptamer-SWCNT complex binds specifically to S. flexneri cells, resulting in a detectable colorimetric response in a test sample involving enzymatic reactions. The assay’s efficacy was validated through sensitivity and specificity evaluations, which demonstrated a detection limit of 51 CFU/mL and selective detection of the target with no signal in different bacterial environments. Comparative analysis with PCR-based methods confirmed the assay’s performance, highlighting its potential as a rapid, cost-effective, and user-friendly diagnostic tool. This study introduces an innovative approach to identifying S. flexneri, which has the potential to improve food safety, environmental monitoring, and public health.